Silicocarnotite: Novel Silicate Bioceramic With Osteogenic Property for Repairing Rat Cranial Critical-Sized Bone Defects - Shao, Yongke; Deng, Fanyan; Chang, Yongyun; Shi, Songqing; Li, Huiwu; Yuan, Yao (Frontiers in Materials, 2022)
Critical sized bone defect is an intractable orthopedic disease, which often fails to regenerate spontaneously and requires additional intervention. Current therapies, including autografts and allografts, are not always satisfactory. Herein, a novel silicon-containing calcium phosphate bioceramic (CPS) with carnotite structure was synthesized. In the present study, CPS were prepared for investigating the biocompatibility and bioactivity in vitro and in vivo in comparison to hydroxyapatite (HA). Our results showed that CPS bioceramics had favourable biocompatibility and rBMSCs could adhere on the surface well in vitro. Moreover, CPS could promote the expression of alkaline phosphatase activity and osteogenic differentiation-related marker genes, including ALP, Runx-2, BSP, OCN and OPN. In vivo, the results of micro-CT, histomorphometry and histology analyses showed that CPS significantly enhanced critical sized calvarial defects healing compared with HA. Overall, the present study demonstrated that CPS bioceramic had satisfactory bioactivities and osteogenic capacities, which might be a potential candidate for the reconstruction of critical sized bone defects.